Maintenance on the Combustion Section Gas Turbine of Unit 2 Gas & Steam Power Plant PLTGU - Prasetiyo, Rafi; Bismantolo, Putra; Suandi, Agus (UNIB Press, 2021)
Gas and Steam Power Plant (PLTGU) is a power plant that utilizes heat from the exhaust gas turbine gas to produce steam which is used as the working fluid of the steam turbine. The components of the PLTGU need to be maintained regularly so that the components can work properly and reduce the risk of damage to these components. Maintenance is an activity carried out to prevent things that are not desirable, such as damage too quickly to the components at the plant. Maintenance of the gas turbine PLTGU shampooing unit is carried out on a time-based basis consisting of combustion inspection (CI), hot gas path inspection (HGPI), and major inspection (MI). Combustion inspection is carried out when the unit has been operating for 8,000 hours. From the results of the inspection carried out on the gas turbine unit of the PLTGU, it was found that several components of the combustion section were damaged. These components are fuel nozzle, cross fire, and combustion liner.